Cosmology with galaxy clusters: An improved multiwavelength analysis - Aymerich G.; Douspis M.; Pratt G.W.; Salvati L.; Soubrié E.; Andrade-Santos F.; Forman W.; Jones C. (EPJ Web of Conferences, 2024)
We provide a new scaling relation using a sample of clusters from a full re-observation by the X-ray Chandra telescope of the Planck ESZ catalogue, and compare it to the results of the Planck collaboration obtained from a smaller sample of XMM-Newton observations. We discuss the expected effects of the change of the scaling relation parameters on the cosmological constraints obtained from the Planck cluster sample, and the remaining steps to obtain final constraints from this new scaling relation.